Analisis Tatakelola Perusahaan Terhadap Harga Saham Pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2017-2020 - Akhmad Imron Rosyadi; Yayan Yanuari (Mulia Pratama, 2021)
This study aims to find out that Non-Performing Loans, Good Corporate Governance, and Capital Adequacy Ratios have a significant effect on stock prices in commercial bank companies listed on the IDX in 2017-2020. The data used in the form of annual financial statements of commercial banks that are used as samples in the study with a period of months and statistical data on economic indicators. The sample of this research was determined by using purposive sampling method in order to obtain 31 companies. The analytical method used is multiple linear regression, namely, classical assumption test, and hypothesis testing. The results showed that partially NPL -had no significant effect on stock prices. GCG has no significant effect on stock prices. CAR has no significant effect on stock prices. Simultaneously NPL, GCG, and CAR have a positive and significant effect on stock prices.